Adsorptive Removal of Methyl Red from Aqueous Solution onto Charred and Aminated Sugarcane Waste - Kour, Jagjit; Pandey, Shankar; Homagai, Puspa Lal; Pokhrel, Megh Raj; Ghimire, Kedar Nath (Journal of Membrane and Separation Technology, 2013)
Adsorptive removal of Methyl Red (MR) from aqueous solution onto chemically modified charred sugarcane waste (CSW) and aminated sugarcane waste (ASW) has been investigated. The surface modification was characterized by FTIR, SEM, elemental analysis and Boehm titration. The effect of pH, contact time and MR concentrations were studied by batch equilibrium method. Maximum dye removal was observed at pH 2 onto CSW while that for ASW at pH 7. The dye can be quantitatively removed onto the surface of these adsorbents at a contact time of 3 h. Maximum adsorption capacity (qmax) for the CSW and ASW were found to be 125.0 mg/g and 142.85 mg/g, respectively. Adsorption kinetic data were tested using pseudo-first order, pseudo-second order and intra-particle diffusion models. Kinetic studies revealed that the adsorptive removal of the dye onto the adsorbents followed pseudo-second order kinetics model. The obtained results indicated an excellent alternative for the treatment of dye contaminated wastewater using such chemically modified sugarcane waste at low cost with better efficiency.